Dynamics and prognostic value of early neonatal mortality in the structure of reproductive loss by the example of Volga Federal District - N.L. Rybkina; O.V. Chumakova ("Paediatrician" Publishers LLC, 2006)
BIRTH AND EARLY NEONATAL MORTALITY RATES OF ALL BORN ALIVE BABIES IN VOLGA FEDERAL DISTRICT AND EACH OF ITS CONSTITUENTS IN 1999-2003 ARE STUDIED. THE RESEARCH FINDINGS REVEAL THE LEADING ROLE OF EARLY NEONATAL MORTALITY RATES IN THE STRUCTURE OF REPRODUCTIVE LOSS. KEY WORDS: BIRTH RATE, EARLY NEONATAL MORTALITY, INFANT MOR TALITY, PERINATAL MORTALITY, STRUCTURE OF REPRODUCTIVE LOSS.